2015
DOI: 10.3748/wjg.v21.i11.3245
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1290 promotes esophageal squamous cell carcinoma cell proliferation and metastasis

Abstract: Our findings suggested that miR-1290 may play an oncogenic role in cellular processes of ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…There are many reports about the positive effects of miR‐1290 on human cancers. For example, miR‐1290 knockdown decreased propagation of non‐small cell lung cancer cells (Kim et al, ), while ectopic miR‐1290 expression potently promoted esophagus cancer cell propagation and metastasis (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports about the positive effects of miR‐1290 on human cancers. For example, miR‐1290 knockdown decreased propagation of non‐small cell lung cancer cells (Kim et al, ), while ectopic miR‐1290 expression potently promoted esophagus cancer cell propagation and metastasis (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-1290 was significantly upregulated in ESCC tissue samples, and ectopic miR-1290 expression potently promoted ESCC cell growth, migration and invasion in vitro (25). miR-140 expression was decreased in the EC tissues and regulated the cell invasion of EC via controlling Slug expression (30).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning chemotherapy in various types of cancers such as breast cancer, lung adenocarcinoma, glioblastoma, and ovarian cancer, recent studies have shown that miRNAs also act in important roles (20)(21)(22)(23)(24). In ESCC, altered expression of miR-1290, miR-655, miR-375 and others, has been observed (25)(26)(27), suggesting that miRNA deregulation plays an important role in ESCC development.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has indicated that SCAI inhibited migration and invasion in human cancers, and SCAI is downregulated in a variety of human tumors [ 35 37 ]. An elegant study defined that SCAI suppressed cancer cell invasion through the transcriptional control of β1-integrin [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%